Large Sclerosing Hemangioma of Lung (Pneumocytoma): A Case Report and Review of the Literature - Jaudah A. Al Maghrabi,; Zuhoor S. Al-Mansouri, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Sclerosing hemangioma of the lung is a rare lung tumor with a well-recognized benign behaviour. This report of a 46-years-old Saudi female, known case of bronchial asthma was presented to the pulmonary clinic in our hospital complaining of cough for six months associated with mild hemoptysis and wheeze. Pathological examination of the resected tumor revealed a well-circumscribed mass measuring 10x6.5x6 cm. Histologically and immunohistochemically, the tumor was a classic SHL. Up to our knowledge this is the largest SHL in the literature. The literature on this topic was reviewed.